Cullers and Guardians: subcultures, attitudes and culling kangaroos - Simmons, Peter; Mehmet, Michael (Penerbit Universiti Kebangsaan Malaysia, 2016)
Traditional approaches to identifying and classifying subcultures (such as class and demographics) are limited in their applicability online. Social media provide an abundant source of insight into subcultures, but the irregular and natural presentation of data often defies systematic analysis and traditional tools. To identify and understand subcultures this study uses appraisal method to analyse comments in public Facebook discussions. It focuses on a contentious issue in Australian society, the culling of kangaroos. The findings are consistent with existing theories about wildlife attitudes and subcultures, suggesting credibility in the sample and findings. Two main groups were identified, referred to here as Cullers, who favour culling and reflect a more general attitude of human dominance over wildlife, and Guardians, who oppose culling and reflect a more general attitude of mutuality in rights and relations for humans and other species. The study supports previous research assertions that attitudes and values are integral to the development of subcultures. The appraisal method provided valuable insight into the complexity of attitudes within the two main groups. The analysis using attitudes helped to reveal economic, environmental, patriotic and rights influences on positions taken by subcultures, and suggests merit in future research using appraisal to identify and account for ‘sub-subcultures’.